2014
DOI: 10.1111/famp.12099
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting the Mental Health of the Caregivers of Children with Asthma in China: Effects of Family Socioeconomic Status, Symptoms Control, Proneness to Shame, and Family Functioning

Abstract: Caregiver mental health is widely considered to be an important factor influencing children's asthma symptoms. The present study aimed to examine key factors that contribute to caregiver mental health in pediatric asthma with a Chinese sample. Two hundred participants reported their family socioeconomic status (SES), proneness to shame, asthma symptoms control of their child, family functioning, and their depression and anxiety symptoms. Results suggested that low family SES, low family functioning, and a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Furthermore, the mental HRQoL of caregivers of children with Autism Spectrum Disorder was lower than that of the general population, their physical HRQoL was however comparable [ 15 ]. Similarly, caregivers of children with asthma showed higher levels of anxiety when compared with the norm [ 16 ]. This may be attributed to the nature of the disease with frequent symptomatic episodes as well as the substantial caregiver responsibility in ensuring a clean and safe environment and regular medication use [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the mental HRQoL of caregivers of children with Autism Spectrum Disorder was lower than that of the general population, their physical HRQoL was however comparable [ 15 ]. Similarly, caregivers of children with asthma showed higher levels of anxiety when compared with the norm [ 16 ]. This may be attributed to the nature of the disease with frequent symptomatic episodes as well as the substantial caregiver responsibility in ensuring a clean and safe environment and regular medication use [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, caregivers of children with asthma showed higher levels of anxiety when compared with the norm [ 16 ]. This may be attributed to the nature of the disease with frequent symptomatic episodes as well as the substantial caregiver responsibility in ensuring a clean and safe environment and regular medication use [ 16 ]. Accounting for these spill-over effects in health economic evaluations has proven challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, over half of the sample had completed university education, the majority were white, and 69% of the families reported incomes of £26,000 or more, which is above the median income in the UK (Office for National Statistics, 2016). Given that asthma can pose significant financial burdens in the family unit (Zhou et al, 2014) and that socioeconomic status has been shown to predict worse anxiety, depression or quality of life outcomes in asthma caregivers (Annett, Bender, DuHamel, & Lapidus, 2003;Celano et al, 2008;Erickson et al, 2003;Zhou et al, 2014), future studies should attempt to include a more diverse sample.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Low-income family in Malaysia refer to household that had income of less than RM3, 860 a month and also known as the B40 family [1]. Previous studies showed that family with low monthly income had low family functioning [2][3][4] and children with high socioemotional behaviour problems [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%